Telaah Kritis E-Katalog Pengadaan Pekerjaan Konstruksi Berbasis Persepsi PPK pada Bidang Cipta Karya - Anestri, Dhea Riesta; Hidayat, Benny; Suraji, Akhmad (Jurnal Talenta Sipil, 2025)
In order to promote efficiency and transparency in the government procurement of goods and services, the use of e-catalogues has been implemented to accelerate information. This study aims to identify the factors contributing to the shortcomings of e-catalog use in construction projects. For this study, interviews were conducted with Pejabat Pembuat Komitmen (PPK)  from construction projects in the Bidang Cipta Karya Dinas Bina Marga Cipta karya dan Tata Ruang Provinsi Sumatera Barat regarding e-catalog version 5. Data analysis was performed using thematic analysis. The results indicate that the e-catalog system is deemed unsuitable for construction projects. Some shortcomings of the e-catalog compared to the tender system in construction projects include the following: 1) insufficient socialization by the government to both service users and providers; 2) regulations that are still biased regarding guidelines for selecting providers and standardizing construction products; 3) limited and incomplete products that are not always available; and 4) ineffective price negotiations, which should only be used for imbalanced prices. High PPK workload due to direct provider selection by the PPK without going through the Pokja. The system is not yet integrated according to needs. Examples include the SIKaP database not being updated and the manual calculation system for selecting service providers, which can lead to typing errors by providers and service users. Therefore, applying procurement principles for goods and services through the e-catalog to construction projects is far from efficient or effective.